2021
DOI: 10.2139/ssrn.3882361
|View full text |Cite
|
Sign up to set email alerts
|

CEO Compensation: Evidence from the Field

Abstract: We survey directors and investors on the objectives, constraints, and determinants of CEO pay. 67% of directors would sacrifice shareholder value to avoid controversy on CEO pay, implying they face significant constraints other than participation and incentive compatibility. These constraints lead to lower pay levels and more one-size-fits-all structures. Shareholders are the main source of constraints, suggesting directors and investors disagree on how to maximize value. Respondents view intrinsic motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For example, in a recent survey,Edmans et al (2021) found that in the decision on setting CEO pay, 65% of board members rank the most important goal to be to attract/retain the right CEO.2 Specifically evidence supports that CEO turnover is dependent on the…”
mentioning
confidence: 99%
“…For example, in a recent survey,Edmans et al (2021) found that in the decision on setting CEO pay, 65% of board members rank the most important goal to be to attract/retain the right CEO.2 Specifically evidence supports that CEO turnover is dependent on the…”
mentioning
confidence: 99%
“…In a similar vein, Gardner, Van Dyne, and Pierce (2004) argue that the pay level “sends an important message to employees about their worth (value) to the organization ” (p. 310). There is also evidence that pay affects one's sense of worth at the very top of hierarchies: Edmans, Gosling, and Jenter (2021) provide survey evidence that CEOs attribute meaning to their pay levels and that decreases in pay may be “ detrimental to the CEO's sense of worth .”…”
Section: Preferences Over Job Prestige and Paymentioning
confidence: 99%
“…This suggests the need for qualitative insights into the operation of the board committee known as the remuneration committee (Remco) (Main et al, 2008(Main et al, , 2011. To understand why optimal risk sharing between executive managers and shareholders may fall short when top pay contracts are specified (Edmans et al, 2021), we aim to illuminate UK top pay decision-making drawing qualitatively on a range of relevant voices.…”
Section: Introductionmentioning
confidence: 99%
“…Attending to contextual specificities suggests to us the merits of adopting institutional theory to shape the focus for investigation and to inform analysis of empirical findings. We examine three linked aspects of Remco-related activity: the role of independent consultants (Ogden and Watson, 2012); the role of HR specialists internal to the organisation (Main et al, 2008); and Remco members' views on their interaction with top pay recipients (Edmans et al, 2021). Flowing from this we set out the following three research propositions (RP): RP1: Executive pay decision-making can benefit from context-informed interaction between pay consultants and Remco members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation